PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT MASMINDO DWI AREA - MH, Rajib; Haedar, Haedar; Halim, Ibrahim (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine and assess how the performance of PT Masmindo Dwi Area employees is influenced by organization, compensation, and work discipline. Through distributing questionnaires, This research uses a quantitative methodology based on causality. The respondents were all employees of PT Masmindo Dwi Area. Meanwhile, purposive sampling was used and there were 100 respondents using SPSS 26 to test the data. The research findings show that employee performance at Pt. Masmindo Dwi Area is positively impacted by corporate culture. The effect of organizational culture on employee performance is significant. A strong organizational culture will result in high employee performance. At Pt. Masmindo Dwi Area, research findings regarding compensation variables have a positive impact on employee performance. Competitive and fair salaries can encourage workers to try harder and do their jobs faster. The research findings of the work discipline variable have a good influence on Pt. Masmindo Dwi Area's employee performance. Employees who practice good work discipline arrive on time, carry out tasks on time, and follow established protocols. Keywords : Organizational Culture, Compensation, Work Discipline